Monster slayer : a Beowulf tale - Patten, Brian, 1946- (Everyone can be a reader., 2025)
One dark night, the sound of music and singing wakes a terrible monster from his sleep in a foul swamp. Warrior after warrior comes to slay the monster, but no one can outwit Grendel. Only the great hero Beowulf stands a chance, but even he is not prepared for the horror that lies in wait.--